Evaluation of the potential SNPs for breeding selection of white spot syndrome virus resistance in Litopenaeus vannamei - Kim Lien, Nguyen Thi; Tung, Nguyen Van; Chi Thanh, Duong; Thu Hien, Nguyen; Ngoc Lan, Nguyen; Thanh Ngan, Nguyen Thi; Huy Hoang, Nguyen; Trang, Trinh Thi; Huu Ninh, Nguyen; Huu Hung, Nguyen (Vietnam Journal of Biotechnology, 2020)
White spot syndrome virus (WSSV) is a dangerous virus causing great damage to shrimp farming. Many genes related to disease resistance mechanisms have been identified and studied. In this study, we amplified and sequenced nine fragments of DNA harboring SNPs in the genes involved in WSSV resistance of white-legged shrimp, Litopenaeous vannamei. Allele frequencies at the SNP loci were recorded and calculated by SPSS statistical software (version 22) in the study groups: the disease shrimp (were infected with WSSV and died) and the resistance shrimp (were infected with WSSV but survived). Six SNPs (in AIF, ALF1, HAE, P53, Rab5B, and TRAF6 genes) were in accordance with Hardy–Weinberg Equilibrium (HWE) (p > 0.05) while three SNPs (in ALF2, BGB, and CAL) were not (p < 0.05). For AIF and ALF1 genes, the frequencies of GG and CC genotypes were significantly different between two groups and were associated with an decreased resistance with WSSV compared to the AA and TT genotypes (p = 0.021 and p = 0.017, respectively). The G and C alleles were associated with a decreased resistance with WSSV (p = 0.000 and p = 0.001, respectively). For HAE gene, the frequency of TT genotype was significantly different between two groups and was associated with a increased resistance with WSSV compared to the TC+CC genotype (OR = 68.750; 95% CI: 11.462–412.381; p = 0.000). For Rab5B gene, the frequency of CC genotype was significantly different between two groups and was associated with an increased resistance with WSSV compared to the TT genotype in all three tested models (p<0.05). The C allele was associated with an increased resistance with WSSV (OR = 3.974; 95% CI: 1.754–9.003; p = 0.001). The above evaluation results suggested that the potential SNPs of these AIF, ALF1, HAE, and Rab5B genes can be used as the molecular markers for breeding selection the resistance to white spot disease in white-legged shrimp L. vannamei.